2017
DOI: 10.1002/pc.24703
|View full text |Cite
|
Sign up to set email alerts
|

An effective non‐covalent grafting approach to functionalize carbon fiber with polyethyleneimine in supercritical fluid to enhance the interfacial strength of carbon fiber/epoxy composites

Abstract: A facile and effective approach to functionalize carbon fiber (CF) by non‐covalent grafting branched polyethyleneimine (PEI) in conventional and supercritical methods was proposed. Fourier transform infrared (FTIR) spectrometry, X‐ray photoelectron spectroscopy, Raman, scanning electron microscopy (SEM), atomic force microscopy (AFM), dynamic contact angle analysis (DCA), and single fiber tensile testing were carried out to characterize the CF reinforcements. Interfacial shear strength (IFSS) and transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…Polyethylenimine (PEI) is a typical water-soluble polyamine, with a polar group (amino group) and a hydrophobic (vinyl) structure that allow it to be bound to different substances [28,29]. It has a wide range of applications in polymer dyes [30], papermaking [31], fiber modification [32] and biomedicine [33]. The PEI molecules contain a large number of amino groups, which have a good selectivity to adsorb the formaldehyde molecules and are suitable for detection of formaldehyde gas [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylenimine (PEI) is a typical water-soluble polyamine, with a polar group (amino group) and a hydrophobic (vinyl) structure that allow it to be bound to different substances [28,29]. It has a wide range of applications in polymer dyes [30], papermaking [31], fiber modification [32] and biomedicine [33]. The PEI molecules contain a large number of amino groups, which have a good selectivity to adsorb the formaldehyde molecules and are suitable for detection of formaldehyde gas [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The amorphous structure on the CF surface could correspondingly increase the active atoms, providing more react sites for subsequent grafting, which was favorable for improving the interfacial adhesion of the CF composite. In addition, the integrated area ratio of the A band to the G band (IA/IG) was widely considered to be an assessment of amorphous carbon structures and some oxygen-and/or nitrogen-containing functional groups and the relative degree of surface functionalization on CF [25,26]. Figure 6 showed that the microstructure heterogeneity changes of the modified CFs surface.…”
Section: Graphitization and Order Degree Of Cf Surface Structurementioning
confidence: 99%
“…There was no suitable interphase for untreated CF/epoxy composite, the crack tip extended perpendicular to the fiber surface directly, which would lead to fiber fracture under low stress. For CF-HBPH/composite, the HBPH interphase could act as a shielding layer which would ease the stress concentration [27]. When the major crack passed to them, HBPH could derive more and more micro-scale cracks, which made the communication process become difficult and intricate, meanwhile, it could prevent the crack tip from directly attacking the fiber reinforcement and efficiently absorb more fracture energy, thereby increasing the composite flexural properties.…”
Section: Dynamic Contact Angle Analysismentioning
confidence: 99%
“…The earliest CFs can be traced back to Edison's application of carbonized cotton yarn. CFs have good in‐plane tensile properties compared with traditional metallic materials , and therefore CF ‐reinforced polymer composites have found a wide range of applications in the aerospace industry and opened up many possibilities for new long‐life products for producers and consumers. However, because CFs produced by the dry‐spray wet‐spinning processes have a low content of active oxygen (O) functional groups and possess low‐roughness surfaces, they do not easily combine with matrices.…”
Section: Introductionmentioning
confidence: 99%